External Debt Sustainability in Selected ASEAN Countries: Do Macroeconomic Data and Institutions Matter? - cahyadin, malik (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 1, Februari 2021 (pp.1-241)DO - 10.24843/JEKT.2021.v14.i01.p03, 2021)
This study attempts to assess indicators of external debt sustainability in seven selected ASEAN countries during 1996-2017 using an indicator-based model. Panel cointegration test was also employed to examine the impact of macroeconomic indicators and institutions on external debt sustainability. There are two indicators of external debt sustainability, namely: (a) EDS1—in which the growth of the external debt should be lower than the growth of GDP, and (b) EDS2—in which the growth of GDP should be greater than the real interest rate. The findings show that macroeconomic indicators and some institutional indicators impact significantly on EDS1 while the macroeconomic indicators—such as, GDP growth, inflation and FDI inflows—and  a single indicator of institutions, i.e., government effectiveness, give a significant impact on EDS2 in the short-run. The speed of adjustment indicates a significant impact on external debt sustainability in the short-run. Furthermore, panel cointegration explains that in the long-run macroeconomic indicators (exclude exchange rate) and institutions have a significant effect on the external debt sustainability. The results of the study aim to contribute to governments policies  in the form of an external debt management policy, pro-growth, pro-investment, price stability and institutional quality improvement at both country and ASEAN levels.